THE SHOREFACE - FAIRWEATHER WAVE BASE ENVIRONMENT OF THE MIDMIOCENE SANDSTONE IN THE CENTRAL PART OF THE MADURA ISLAND - MAC. Endharto (Scientific Contributions Oil and Gas, 2006)
As mentioned in the previous paper (Endharto, 2005) this paper is part of the series of the depositional model of the Ngrayong Sandstone, which takes part especially in the central part of the Madura Island. This study also examines physical evidence of the best exposure of the study area. The central part is located between 07 01' 18" S - 113 32' 56" E and 07 04' 55" S- 113 36' 54" E, covering the area of Tanjung - Pasean to the north and Mentok - Kertengeneh - Sentol to the south. (Figure 1). The Geological work was carried out during June - July 2005, where the particular attention was concentrated within the central region of the island. There are 3 major key outcrop areas were studied and assigned for the depositional setting of this area (i.e., Tanjung toward Pasean River, Mentok - Kertengeneh Oil Field and Sentol Daya sections). This worked has attempted to sort it out both vertical and horizontal sections with applying the stratigraphic measuring sections (outcrop/surface logs), horizontal distance using passing compass, supported by petrography and paleontology analysis, and trying to look at the internal sedimentological structures to get into broadly image of the depositional system within this area.